Reliability of ergonomic exposure assessment: comparing the Strain Index and the OCRA Checklist - Paulsen, Robert James, author; Gilkey, David, advisor; Rosecrance, John, committee member; Reiser, Raoul, committee member (Colorado State University. Libraries, 2013)
Occupational ergonomists utilize a variety of observational methods to identify jobs that elevate workers' risk for developing work-related musculoskeletal disorders. Internationally, the Strain Index (SI) and the Occupational Repetitive Actions (OCRA) Checklist are two of the most popular upper extremity exposure assessments available. Both are founded on similar biomechanical and epidemiological principles, but their approach to quantification and estimation of risk factor magnitude is quite different. The purpose of the present study was to analyze the inter-method reliability of SI and OCRA Checklist exposure assessments. An additional aim was to estimate the inter-rater reliability of both methods. Twenty-one cheese-processing jobs were video recorded at an Italian facility. Eight individuals with occupational health training were recruited to rate every job using both the SI and OCRA Checklist. Inter-method reliability was characterized using kappa coefficients and Spearman correlations, and inter-rater reliability was characterized using intraclass correlation coefficients. Strain Index and the OCRA Checklist assessments produced moderately reliable results, generally classifying the same job exposures to physical risk factors similarly. Systematic bias due to rater effects was observed, and a lack of individual rater familiarity with one or both methods may have contributed to this bias. Further, the assessment of multi-task jobs was associated with lower inter-method reliability than what was observed for simpler jobs. Inter-rater reliability of the SI and OCRA Checklist summary scores and exposure classifications suggested moderate intra-method reliability. Summary scores may be a reliable measure of exposure to meet the needs of epidemiologists and occupational health and safety practitioners.
Keywords: ergonomics; exposure assessment; musculoskeletal disorders; OCRA; reliability; Strain Index